2022
DOI: 10.1002/slct.202103901
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antibacterial Activity, and Molecular Docking Study of Bispyrazole‐Based Derivatives as Potential Antibacterial Agents

Abstract: Development of novel antibacterial agents is one of most important aims in the field of medicinal chemistry and drug discovery. A new series of bispyrazole derivatives were synthesized with moderate to excellent yields ranging from 68 to 83 %. The structures of the newly synthesized compounds were confirmed using NMR, GC, IR techniques. The prepared derivatives were screened against Gram-positive bacteria (S. aureus and B. subtilis) and Gram-negative bacteria (E. coli and P. aeruginosa). All of the new compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Merck silica gel GF254 plates were used for analytical TLC. 1 H and 13 C NMR spectra were obtained on a Varian INOVA400 (400 MHz for 1 H and 101 MHz for 13 C) in CDCl 3 or DMSO-d 6 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Merck silica gel GF254 plates were used for analytical TLC. 1 H and 13 C NMR spectra were obtained on a Varian INOVA400 (400 MHz for 1 H and 101 MHz for 13 C) in CDCl 3 or DMSO-d 6 .…”
Section: Methodsmentioning
confidence: 99%
“…The structures of these compounds were characterized by 1 H NMR and 13 C NMR, as well as electrospray ionisation mass spectrometry (ESI-MS) analysis. The 1 H NMR results showed chemical shifts around 13.2 for the hydrogen on the amide, 12.3 for the hydrogen on the carboxyl group, multiple peaks between 7.5-8.0 for the hydrogen on the aromatic ring, multiple peaks between 1.2-3.0 for the hydrogen on the sixmembered ring, and around 1.0 for the hydrogen on the methyl group.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that five compounds of newly synthesized have IC 50 values less than 5.95 µM. In our continuous attempts to develop novel potent bioactive agents ( Abdel-Jalil et al, 2015 , El-ajaily et al, 2019 , El-Barasi et al, 2020 , Eleya et al, 2011 , Hussain et al, 2008 , Ibad et al, 2011 , Kamel et al, 2022a , Kamel et al, 2022b , Mahal, 2015a , Mahal et al, 2010 , Mahal et al, 2011 , Mahal et al, 2015b , Mahal et al, 2015c , Mahal et al, 2019 , Mahal et al, 2021 , Marzano et al, 2022 , Mohapatra et al, 2021 , Salman et al, 2011 , Salman et al, 2020 , Salman et al, 2022 , Yang et al, 2017 , Yang et al, 2018 , Zinad et al, 2020a , Zinad et al, 2020b , Zinad et al, 2020c , Zinad et al, 2020d , Zinad et al, 2021a , Zinad et al, 2021b , Zinad et al, 2022 , Zinad et al, 2023a , Zinad et al, 2023b ), we aim at this study to investigate the molecular docking and DFT calculation of potent anticancer agents of tetrahydrocurcumin.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Moreover, nitrogen-containing heterocyclic compounds are significantly found in several naturally occurring plant materials. [10] The N-heterocycles are attractive targets in organic and medicinal chemistry [11] due to their vast biological applications including anti-tumor, [12] antihypertensive, [13,14] antiulcer, antifungal, [15] anti-bacterial [16] antimalarial, and antiallergic activities. [17,18] Nowadays, one of the specific areas in green chemistry is the search for environmentally benign reaction media to replace the commonly used hazardous or toxic organic solvents/metal catalysts in chemical reactions.…”
Section: Introductionmentioning
confidence: 99%